Are Minority and Women Candidates Penalized by Party Politics? Race, Gender, and Access to Party Support. (September 2021) - Fraga, Bernard L.; Hassell, Hans J. G.
Racial/ethnic minorities and women continue to be underrepresented in public office in the United States. Here, we evaluate the role of general election political party support for women and minorities in structuring these inequalities, as a key part of general election success is support from party networks. With detailed data on party support and the demographics of congressional candidates, we use two difference-in-differences strategies to leverage within-district and candidate-constant change over time. Thus, we are able to separate the effect of race/ethnicity and gender from other factors we demonstrate to be associated with party support. We find that, all else equal, Democratic and Republican minority nominees do not receive less support than their white counterparts. We also find that white women receive more party support from Democrats than Democratic men or minority women in the general election and that this support is more responsive to changes in electoral competitiveness. These findings suggest that party elites may provide additional support to candidates from underrepresented groups in the general election to broaden their appeal to voters.